Application of ICT for Efficient and Transparent Price Discovery: an Analysis of e-Tendering of Agricultural Commodities in Karnataka - Shalendra; Purushottam Sharma; K.C. Gummagolmath (Journal of Agricultural Extension Management, 2014)
State Governments have taken a number of initiatives from time to time, ranging from regulations to reforms in agricultural marketing, to ensure transparent and efficient price discovery mechanisms in agricultural wholesale markets. Introduction of electronic tender system in wholesale markets, by the State Government of Karnataka is one such initiative aimed at bringing in transparency in the transaction process and eliminating various malpractices associated with the conventional method of transactions at APMCs. The impact of the initiative mainly on prices and arrivals of agricultural commodities has been analyzed and presented in the present paper. The analysis reveals positive impact of electronic tender on arrivals, prices and has helped in scientific discovery of prices. The system may be utilized effectively in enhancing trade competitiveness by integrating different markets across the state. The system may also facilitate the integration of concepts like warehousing, grading, electronic payment, electronic weighment, packaging, branding, pledge financing, etc. Grade based electronic tender may also help in achieving the goal of having a Single Integrated Market